Globalising myths of survival: post-disaster households after Typhoon Haiyan. Issue 11 (23rd September 2020) - Su, Yvonne; Tanyag, Maria
Abstract: Disasters, as forms of crisis, offer opportunities to place in sharper focus historical and ongoing inequalities in the production and reproduction of everyday life. The opportunity for transformative change, however, risks being lost when representations of disaster increasingly obscure and silence the full costs and complexity of post-disaster recovery. This article identifies the construction and subsequent proliferation of survival myths in the context of the Philippines after the 2013 Typhoon Haiyan disaster from a feminist perspective. Using data from in-depth interviews and surveys, we examine the experiences of middle and lower-class households in three heavily affected communities in Tacloban City to challenge three dominant survival myths: the local culture of mutual assistance ( bayanihan ), the endless resourcefulness of Filipinos in times of crisis, and the positive contributions of overseas migrant remittances. We argue that these myths have served as tools for reinforcing gendered inequalities during and after the disaster because they render invisible the feminisation of care burdens, and contribute to gender gaps in ensuring accountability for post-disaster governance. The evidence from this research underscores the importance of interrogating how similar survival myths are being globalised in disaster governance at the expense of forging substantive gender equality in post-disaster settings.